Photosynthetic physiology of Scenedesmus sp. (Chlorophyceae) under photoautotrophic and molasses-based heterotrophic and mixotrophic conditions. Issue 6 (1st November 2017) - Kamalanathan, Manoj; Dao, Ly Hai Thi; Chaisutyakorna, Panjaphol; Gleadow, Ros; Beardall, John
Abstract: Heterotrophically grown cells of a newly isolated strain of Scenedesmus sp. retained their photosynthetic pigment content after prolonged darkness. When these cells had reached an apparent stationary phase and were subsequently exposed to light (mixotrophy), growth rapidly resumed and the biomass increased by 5.5-fold relative to photoautotrophically grown cultures and doubled compared with heterotrophic cultures. Although it is expected, and supported by the majority of reports in the literature, that dark acclimation of algal cultures should lead to eventual loss of photosynthetic pigments, some algae defy these expectations and synthesize and retain their photosynthetic pigments independent of light, despite the high associated maintenance costs. Here we examined the photosynthetic activity of heterotrophically grown cells in an attempt to explain this variance, using Scenedesmus sp. as a model organism. The photosynthetic capacity of heterotrophically grown cells was comparable with that of autotrophically grown cultures, associated with an interesting set of changes to the photosynthetic apparatus that includes lower nonphotochemical quenching, chlorophyll content, absorption cross-sectional area, higher connectivity between reaction centers, higher electron transport flux per reaction center, and probability at t = 0 that a trapped exciton moves an electron into the electron transport chain beyond the primary quinone electron acceptor, and performance index. As a result, when these heterotrophically grown cultures were transferred back to light, they were still able to perform photosynthesis and enhance overall growth, which was otherwise limited in complete darkness.